Scientometric Analysis of Entrepreneurial Orientation: Research Mapping and Opportunity Areas - José Rubiales-Núñez; Andrés Rubio; Luis Araya-Castillo; Hugo Moraga-Flores; Carlos Gómez-Pantoja (Administrative Sciences)
This research presents a comprehensive scientometric analysis of Entrepreneurial Orientation (EO), a fundamental concept in strategic management and business performance. Through a bibliometric approach, 4314 articles indexed in the Web of Science from 1975 to 2024 were analyzed using advanced network analysis tools such as VOSviewer to examine the evolution of scientific production, citations, authors, journals, institutions, and the most influential countries in the field. The findings reveal an exponential growth in “EO” research over the past decades, with a high concentration of scientific output in the last eight years. The United States leads in publication volume and citations, followed by other countries with an increasing contribution. Co-authorship patterns and academic collaboration clusters have been identified, consolidating key research lines that link “EO” with innovation, market orientation, and business performance. This study provides a comprehensive perspective on the evolution of “EO” research, offering valuable insights for academics, policymakers, and professionals interested in new theoretical directions and practical applications that foster knowledge development and business competitiveness.